Pengaruh Pemberian Employee Stock Option Plan (ESOP) pada Kinerja Perusahaan dan Implikasinya Terhadap Nilai Perusahaan - Dharmala, Ni Wayan Dea; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p05, 2019)
The company is a contract between the owner of the company (principal) and management (agent) which is called the agency relationship. In this connection, there is often a conflict of interest. One of the principal ways to minimize differences in interests is to provide compensation to employees in the form of a share ownership program (ESOP). This study aims to determine the effect of giving ESOP on company performance and its implications for firm value. Samples obtained based on the purposive sampling method are 48 observations. Data collection uses non-participant observation methods. The data analysis technique used is path analysis. The results showed that ESOP had a positive effect on company performance, company performance had a positive effect on company value, ESOP had no effect on company value, and ESOP had an effect on firm value through company performance. Keywords : Employee stock option plan, company performance, company value